Poster 131: Open Bankart versus arthroscopic Bankart with remplissage for anterior glenohumeral instability with subcritical glenoid bone loss. Issue 7 (30th July 2022) - Bedrin, Micheal; Yow, Bobby; Putko, Robert; Culp, Hunter; Dickens, Jonathan; Tropf, Jordan
Objectives: The optimal surgical technique for the management of subcritical glenoid bone loss (GBL) with or without engaging Hill Sachs (HS) lesion is unknown. Open Bankart and arthroscopic Bankart repair with remplissage have been proposed as potential treatments however no comparative studies exists. The goal of this study was to define failure rates and associated risk factors for patients with subcritical GBL undergoing either open Bankart or arthroscopic Bankart with remplissage. Methods: A consecutive series of arthroscopic Bankart stabilizations with remplissage or open Bankart repairs were performed by sports-medicine certified and fellowship trained orthopaedic surgeons from 2010-2019 . Minimum follow up was 2 years, and shoulders with glenoid bone loss <3% or >25%, multidirectional instability or hyperlaxity were excluded. Shoulders were additionally excluded if magnetic resonance imaging (MRI) was not available at the time of preoperative evaluation or the patient was lost to follow-up. All shoulders were evaluated for glenohumeral bone loss using the perfect circle technique on the sagittal en-face MRI as well as for bipolar lesions according to the on/off-track method of Diagacomo et al. The primary outcomes of interest were recurrent instability (subluxation or dislocation) and revision stabilization. A power analysis was conducted based on a projected failure rate of 10%, alpha 0.05, and power of 80% which determined that 28 patients would be needed per group to detect a 4-fold difference in failure rate. Multivariable logistic regression models were used to assess the relationships of outcomes with surgical technique, primary vs revision surgery, and track. Results: Thirty-one patients (31) with open Bankart and twenty eight (28) patients with arthroscopic Bankart and remplissage met inclusion criteria. The mean age was 25.9 years old (18-46) and mean follow-up 4.7 years. There was no difference in baseline age (remplissage 27.8 years, open Bankart 24.5 years), glenoid bone loss (remplissage 13.8%, open Bankart 11.1%), off-track HS (remplissage 13, open Bankart 17) or primary versus revision surgery (primary remplissage 18/28, primary open Bankart 14/31) between cohorts. The failure rate in the open Bankart cohort was 6.5% (2/31) with 2 dislocations, multiple subluxations, resulting in 2 revisions. The failure rate of the arthroscopic Bankart remplissage cohort was 7.1% (2/28), 2 dislocations, multiple subluxations, resulting in 2 revisions. Multivariate regression analysis did not identify age, gender, procedure, GBL, index vs revision surgery, or on/off track as predictors of failure. Subgroup analysis of patients with on- vs off-track HS lesions as well as primary vs revision surgery showed no difference in patient baseline characteristics including GBL, and no difference in failure rates between patients with open Bankart and remplissage. Conclusions: Bankart and arthroscopic Bankart with remplissage are both effective at treating anterior instability with subcritical GBL. No differences in failures or complications was observed between our arthroscopic Bankart with remplissage and open Bankart cohorts.